Generative AI for Ecological Research and Ecology Education: A Systematic Literature Review - Djohar Maknun; Jajang Aisyul Muzakki; Ipin Aripin; Bambang Ekanara (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2026)
Gen AI has been applied widely in applied science research, but its use in ecological research and ecology education is still rarely studied. This research aims to systematically examine the use of Gen AI in ecological research and ecology education. This study applied the PRISMA method to analyze relevant studies in Scopus. The study found 23 relevant articles related to the use of Gen AI in ecological reseach (n=17) and ecology education (n=7). In the field of ecological research, Gen AI is utilized for ecological monitoring, landscape ecology, species identification, industrial ecology, conservation, human ecology, and as an ecological research tool. Gen AI in ecology education is used to personalize learning content, support an AI-based automatic assessment system, enable digital field simulations, and foster student innovation and creativity. This study emphasizes the importance of establishing clear guidelines and providing training for both lecturers and students to optimize the benefits of Gen AI and to mitigate the associated risks. The findings of this study are expected to provide recommendations for educators and researchers on utilizing AI to support ecological research and the effective teaching of ecology. This research has practical implications regarding the importance of digital literacy and ethical AI use in the academic context.